Effectiveness of E-Learning Management During Covid- 19 Pandemic in Indonesia - Singgih Purnomo; Suci Purwandari; . Junaedi (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
This research aims to analyze the effectiveness of e-learning management during the Covid-19 pandemic in Indonesia with Delone and Mclean Model and Virtual Learning Effectiveness approach. The research method used is quantitative, with a sample of students in Indonesia. The data collection method uses an online questionnaire sent by email and an actual phone number. The data analysis method uses structural equation modeling based on Partial Least Square (PLS). This study found empirical evidence that technological factors, namely the quality of the system and the quality of information, and psychological factors, namely self-efficacy and human factors that are the services of lecturers, have a significant effect on user perception and user satisfaction. User perception and user satisfaction have a significant effect on the effectiveness of e-learning. This study develops research models DM and VLE. Future research planned to extend this research model into an integrated model structure that could help define factors in the performance of e-learning systems and important e-learning success factors, or superior to conventional face-to-face learning systems